TREATMENT SPECIFICS AND CLINICAL OUTCOMES IN PATIENTS WITH ACUTE CORONARY SYNDROME AND ANAEMIA: RECORD REGISTRY RESULTS - A. D. Erlikh; N. A. Gratsianskyi (Российский кардиологический журнал, 2012)
Aim. To analyse the treatment characteristics and specifics in patients with acute coronary syndrome (ACS) and anaemia, based on the data from the Russian ACS registry (RECORD). Material and methods. The recruitment of the patients (November 2007 – February 2008) was performed, using the independent Russian ACS register RECORD. Results. The study included 796 patients (mean age 64,7±12,1 years; 57,2% men). ACS with ST segment elevation (ST ACS) was registered in 246 patients (30,1%), while ACS without ST segment elevation (non-ST ACS) was observed in 550 patients (69,9%). Anaemia at admission was registered in 228 participants (29,0%). The anaemia group had a higher proportion of elderly patients – those with diabetes mellitus, heart failure in anamnesis and at admission, and high risk by the GRACE scale. These patients were less often hospitalised in “invasive” hospitals. In hospital, anaemic patients less often received clopidogrel and underwent reperfusion in ST ACS or invasive procedures in non-ST ACS. Low baseline levels of haemoglobin (<110 g/l) independently predicted the risk of in-hospital death (odds ratio 4,6; 95% confidence interval 1,9–11,2; p=0,001). Anaemic patients had significantly higher risk of in-hospital death, compared to their non-anaemic peers (10% vs. 5,2%; p=0,012). In the group of anaemic patients with non-ST ACS, the risk of adverse outcomes (death or new myocardial infarction during hospitalisation) was significantly lower in those who underwent percutaneous coronary intervention (PCI) (4,1% vs. 18,2%; p=0,04) or PCI and coronary artery bypass graft surgery (3,6% vs. 17,6%; p=0,013). However, in non-anaemic patients, no such difference was observed: 5,8% vs. 4,2% (p=0,6) and 5,6% vs. 4,1% (p=0,6), respectively. Conclusion. First, in RECORD Registry participants, haemoglobin levels ><110 g/l independently predicted the risk of in-hospital death. Second, anaemic patients were characterised by a higher number of risk factors, lower rates of invasive procedures, and a significantly higher risk of in-hospital death. Third, in patients with non-ST ACS and anaemia, the absence of coronary interventions was linked to a significantly higher risk of death or new MI during hospitalisation. Russ J Cardiol 2012, 5 (97): 12-16 Key words: acute coronary syndrome, registry, anaemia><110 g/l) independently predicted the risk of in-hospital death (odds ratio 4,6; 95% confidence interval 1,9–11,2; p=0,001). Anaemic patients had significantly higher risk of in-hospital death, compared to their non-anaemic peers (10% vs. 5,2%; p=0,012). In the group of anaemic patients with non-ST ACS, the risk of adverse outcomes (death or new myocardial infarction during hospitalisation) was significantly lower in those who underwent percutaneous coronary intervention (PCI) (4,1% vs. 18,2%; p=0,04) or PCI and coronary artery bypass graft surgery (3,6% vs. 17,6%; p=0,013). However, in non-anaemic patients, no such difference was observed: 5,8% vs. 4,2% (p=0,6) and 5,6% vs. 4,1% (p=0,6), respectively. Conclusion. First, in RECORD Registry participants, haemoglobin levels < 110 g/l independently predicted the risk of in-hospital death. Second, anaemic patients were characterised by a higher number of risk factors, lower rates of invasive procedures, and a significantly higher risk of in-hospital death. Third, in patients with non-ST ACS and anaemia, the absence of coronary interventions was linked to a significantly higher risk of death or new MI during hospitalisation.